Upaya Kepala Madrasah dalam Meningkatkan Mutu Pendidikan di MI Ma’arif Giriloyo II Bantul Yogyakarta - Aufa Aufa (Jurnal Pendidikan Madrasah, 2016)
This research is a field that discuss management headmaster in improving the quality of education in MI Ma'Arif Giriloyo 2 Bantul Yogyakarta, which are qualitative. The results of this study were (1) the management headmaster in MI Ma'Arif Giriloyo 2 Bantul Yogyakarta include: educator, managerial, administrator, supervisor, leader, innovator and motivator. (2) improving the quality of education can be accomplished by efforts to improve the professionalism of teachers by providing opportunities for teachers to continue their studies to a higher level and includes the seminars, workshops, and computer training. Religious activities and provide additional tutoring subjects to students for national exams. (3) factors affecting the implementation of management headmaster include factors: the availability of funds, personnel, infrastructure and the presence of MI 1 that become obstacles for MI 2 in making innovations, because MI 1 and MI 2 under the auspices of the same foundation.